Correction: Ultra-fast and highly sensitive enzyme-free glucose biosensing on a nickel–nickel oxide core–shell electrode. Issue 83 (16th November 2017) - Begum, Halima; Ahmed, Mohammad Shamsuddin; Jeon, Seungwon
Abstract : Correction for 'Ultra-fast and highly sensitive enzyme-free glucose biosensing on a nickel–nickel oxide core–shell electrode' by Halima Begum et al., RSC Adv., 2017, 7, 3554–3562.